Complicity by omission in the punishable act of sexual abuse of children (Legal journal - Research in Legal and Social Sciences, 2022)
This paper studies complicity by omission in the punishable act of sexual abuse of children, in order to determine whether this type of crime is applicable in Paraguayan criminal law. In this sense, according to the Criminal Code, the criminally relevant human behavior consists of two types -essentially- action and omission, and omission has two modalities, proper and improper.In order to advance in the study, a description of the punishable act of sexual abuse of children has been made, for which it is important to understand that this act is one of the so-called crimes committed at one’s own hand. A qualitative approach with a non experimental design was used for the research. A hermeneutic study was carried out by means of a bibliographic review of the main exponents of the theory of improper omission, to then elaborate a practical case based on this criminal modality, according to the experience of the fiscal praxis, to elaborate the category of analysis of the improper omission in this punishable act as accomplice. Finally, the main theory of the identified problem was used to interpret it from a practical case and to design a theory based on national legislation. It is concluded that it is possible to commit the punishable act of sexual abuseof children as accomplice, by omission.
Keywords: child sexual abuse; improper omission; self-inflicted crime